EVALUATION OF ADAPTATION AND WEAR SIMULATION OF INNOVATIVE TOOTH-COLORED PRIMARY POSTERIOR CROWNS - Mahmoud El-Said Ahmed Abd El-Aziz; Mohamed Aboelkasme Wakwak; Yousef Hamed Abokhlifa; Alaa Nabil Abbas; Salam Mohamed EL Araby; Abdelhamid Abuelyazid Eissa; Mohamed Galal Aboelsoud; Ashraf Marawan El Azzazy; Waled Omar Ameen Kadour; Alaa N. Syam (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Purpose: The aim of this study was to evaluate the adaptation and wear simulation of innovative tooth-colored primary posterior crowns, specifically comparing ceramic (Zirconia) crowns and glass-reinforced fiber composite (FRC) crowns.Material and methods: Fourteen posterior crowns from two manufacturers were used: Elephant Plus Zirconia crowns (Ceramic) and Figaro Glass-reinforced fiber composite crowns (FRC). Crowns were cemented to their respective master dies and the vertical marginal gaps were measured using a digital microscope and analyzed with Image J software. A wear simulation was performed utilizing a programmable logic controlled four-station multimodal ROBOTA chewing simulator, which included a thermocyclic protocol , simulating 3 months of clinical chewing conditions. Surface roughness was measured using optical profilometry and analyzed with WSxM software.Results: The FRC group showed a significantly greater vertical marginal gap mean score (69.36 ± 8.84 µm) compared to the Ceramic group (26.44 ± 7.05 µm) (p < 0.0001). Surface roughness results indicated no significant difference between the groups before wear simulation, with the Ceramic group at 0.2496 ± 0.03 µm and the FRC group at 0.2395 ± 0.22 µm (P=0.494). After wear simulation, the roughness remained statistically non-significant between the Ceramic group (0.2609 ± 0.025 µm) and the FRC group (0.2533 ± 0.023 µm) (P=0.5667).Conclusion: Ceramic crowns demonstrated superior marginal adaptation compared to FRC crowns, making them a preferable choice for scenarios requiring high precision. However, both materials exhibited similar wear resistance and surface roughness characteristics, indicating their viability for long-term restorative solutions in pediatric dentistry. Further research with larger sample sizes and long-term clinical trials is recommended to validate these findings.